Critical analysis on Aceh educational strategic planning from Islamization of education perspective - Ramli, Affan (Institute of Education, International Islamic University Malaysia, 2013)
Aceh aspires to be a Muslim state supported by an Islamic education System. For this purpose Aceh Educational Strategic Planning (AESP) 2007-2012 was formulated as guidance for the implementation of Islamization of education in Aceh. This study aims to critically assess the strategies of Islamization of education in Aceh as described in the AESP 2007-2012 policy document. It aims to investigate (1) whether the AESP document provides the appropriate concept and practical guidance in implementing the Islamization of education and (2) on how recommendations of the first four World Conferences on Muslim Education can be adopted as a basis in improving the strategies. The study employed the qualitative research methods of (1) analyzing relevant documents produced by the Majlis Pendidikan Daerah Aceh (MPDA/ Aceh Regional Education Assembly) which was the mandated institution responsible for developing the concept and strategy of Islamization of education; and (2) interviews with two key informants from MPDA and the Aceh Department of Education. The concept and strategies of Islamization of education were analyzed based on Islamic education theories proposed by Syed Naquib Al-Attas and Syed Ali Ashraf, and the recommendations of the first four World Conferences on Muslim Education. The study found that the AESP 2007-2012 lacks comprehensive concepts and practical guidance for Islamization of education to be implemented by the Aceh Department of Education, schools and universities. This was evident from the lack of attention to Islamization of the philosophy and the aims of education, curriculum, disciplines (textbooks), and teaching methods; further, the Aceh Department of Education was only able to extend the hours of religious instruction for elementary school. The study concludes with a proposal of a set of measures to improve the future strategy of the Islamization of education in Aceh.